Vertically Oriented Femoral Neck Fractures: A Biomechanical Comparison of 3 Fixation Constructs. Issue 7 (July 2017) - Johnson, Joey P.; Borenstein, Todd R.; Waryasz, Gregory R.; Klinge, Stephen A.; McClure, Philip K.; Chambers, Alison B.; Hayda, Roman A.; Born, Christopher T.
Abstract : Objectives: To compare the static and dynamic mechanical properties of a modified crossed cannulated screw (CS) configuration, the inverted triangle (IT) cannulated screw configuration, and a compression hip screw (CHS) with derotation screw in Pauwels type III femoral neck fractures. Methods: Thirty synthetic femora were divided into 3 groups, and vertical femoral neck osteotomies were made. Ten osteotomized femora were fixed with a CS configuration, 10 were fixed with 3 parallel screws in an IT configuration, and the remaining 10 osteotomized femora were fixed with a CHS construct. All groups were tested using a cyclic (up to 15, 000 load cycles) axial loading protocol, and survivors were statically loaded to failure. Cycles to failure, load to failure, and stiffness were calculated. The Kaplan–Meier method was used to estimate survival functions and were compared among fixation methods. The relationship between construct structural properties (maximum load and stiffness) and treatment were assessed using general linear modeling. Results: All CHS fixation constructs survived the 15, 000 cycle loading protocol. They endured longer ( P = 0.034) than the CS fixation constructs (mean failure 13, 332 cycles), but were not different from IT fixation constructs (mean failure 13, 592 cycles). Maximum loads to failure for CS (3870 N) and IT (3756 N) fixation constructs were not different, but were less ( P < 0.0001) than the maximum loads to failure for the CHS fixation constructs (5654 N). These findings parallel the results of the axial stiffness measurements: CS fixation constructs (663.01 N/mm) were not stiffer than IT fixation constructs (620.0 N/mm), but were less ( P = 0.0005) than the axial stiffness of the CHS fixation constructs (1241.86 N/mm). Conclusions: The biomechanical performance of the CHS fixation method was superior to both the CS fixation method and the IT fixation method using a synthetic femoral model and this test protocol. Biomechanical performance of the latter 2 groups was indistinguishable. We recommend the use of CHS with the derotational screw construct for Pauwels III femoral neck fractures whenever possible. Abstract : Supplemental Digital Content is Available in the Text.